ENVIRONMENT CIVIL LAW ENFORCEMENT - Widiyanto, Indra; Rijadi, Prof. Dr. Prasetijo (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2023)
Environmental pollution is a complex problem with both short-term and long-term risks. Regulations that regulate natural resource utilisation activities serve as preventive and repressive steps for environmental issues. Environmental law is a form of government concern for complex environmental problems, through law enforcement that can be pursued through administrative, criminal, and civil law. Therefore, this research aims to find out and understand environmental law enforcement efforts through legal aspects. This research type is normative legal research. In normative legal research using statutory, conceptual, historical, and comparative approaches. In supporting this research, 2 sources of legal materials are used, such as (1) primary legal sources, which consist of parliamentary legislation, subordinate legislation, judicial decisions and reported tribunals; (2) secondary legal sources, such as all legal literature that is not a formal memorandum of law (encyclopaedias, case summaries, textbooks, journals, dictionaries, indexes and bibliographies). This research indicates that in the enforcement of civil environmental law, there are litigation and non litigation. In addition, the settlement of disputes can be conducted through condemnatory verdicts, declaration verdicts, and constitutief verdicts. In civil law, legal sanctions can be an obligation to fulfil achievements (obligations) associated with the requirements of obligations according to Article 1365 BW (Civil Code).